A Surprising Lead Point in an Ileocolic Intussusception. Issue 2 (17th February 2023) - Scheier, Eric; Brenner, Galit; Oren, Shachar
Abstract: Appendicitis and intussusception are 2 of the most common abdominal emergencies in children and have high rates of morbidity if not treated promptly. However, only rarely do they occur together. We present a case in which clinical suspicion for intussusception was not high. Point-of-care ultrasound (POCUS) was performed in the pediatric emergency department, revealing both ileocolic intussusception and appendicitis. This case reinforces the importance of maintaining a broad differential diagnosis in unclear clinical scenarios and of the potential utility of POCUS. In our case, identification of intussusception on POCUS facilitated expeditious treatment, identification of the lead point, and allowed the treating physicians to prepare for the possibility of surgical management.